A new species of barred frog, Mixophyes (Anura: Myobatrachidae) from south-eastern Australia identified by molecular genetic analyses - Mahony, Michael J; Bertozzi, Terry; Guzinski, Jaro; Hines, Harry B; Donnellan, Stephen C (Zootaxa, 2023)
Mixophyes are large ground-dwelling myobatrachid frogs from eastern Australia and New Guinea. Several of the species found in mid-eastern and south-eastern Australia are listed as threatened, due largely to declines presumably caused by the amphibian disease chytridiomycosis. Given the wide distribution of several of these species and that their distributions cross well-known biogeographic boundaries that often correspond to deep genetic breaks or species boundaries among closely related vertebrates, we undertook a molecular genetic assessment of population structure across the range of each species to determine the presence of undescribed species. Of the four species of Mixophyes subject to molecular population genetic analyses, one, the Stuttering Frog (Mixophyes balbus), showed a level of diversity consistent with the presence of two species. Morphometric, meristic and bioacoustic analyses corroborate these distinctions, and a new species is described for the populations south of the Macleay River valley in mid-eastern New South Wales to east Gippsland in Victoria. Applying the IUCN Red List threat criteria the new species meets the conservation status assessment criteria for Endangered 2B1a,b because its extent of occupancy and area of occupancy are below the threshold value and it has declined and disappeared from the southern two thirds of its distribution over the past 30 years.